Optimized preparation method of natural gas pipeline transportation plan based on minimum energy consumption - Shuo JIN; Xifeng NING; Jiayan MENG; Yunfeng SUN (You-qi chuyun, 2021)
At present, the natural gas pipeline transportation plan is mainly prepared based on the artificial experience, which requires considerable time and energy, unfavourable for the overall optimization of the plan. In order to enhance the preparation efficiency and scientificity of the natural gas pipeline transportation plan, the artificial experience for preparation of the natural gas pipeline transportation plan was encoded by summarizing the existing preparation methods, and auxiliary software was developed to seek a feasible solution for the pipeline transportation plan. With the constraints of supply and sales balance and the design throughput of the natural gas pipeline network, and with the minimum energy consumption of the gas pipeline network as the optimization target, a natural gas pipeline network optimization model was established based on the statistical and fitting analysis on the massive historical data of energy consumption and throughput, and the optimal feasible solution was sought with the optimization method. Furthermore, the fitting process between unit consumption and turnover volume was elaborated by taking two trunk lines as the examples. The new optimization method could provide an efficient and scientific optimized preparation method of pipeline transportation plan for complex natural gas pipeline network system.